Clinical and Laboratory Phenotype Variability in Type 2M Von Willebrand Disease - Doruelo, Ashley L. (J Thromb Haemost, 2017)
BACKGROUND: Von Willebrand factor (VWF) is a multimeric coagulation factor that tethers platelets to injured subendothelium. Type 2M von Willebrand Disease (VWD) is characterized by a qualitative defect in VWF with preserved multimer distribution. OBJECTIVES: Through the Zimmerman Program for the Molecular and Clinical Biology for VWD, five VWF sequence variations were studied in subjects diagnosed with type 2M VWD. METHODS: Bleeding phenotype was assessed using the ISTH bleeding assessment tool. Full length VWF gene sequencing was performed for each subject. Each variant was placed into a recombinant VWF vector using site-directed mutagenesis and expressed in HEK293T cells as homozygous or heterozygous VWF. Variant expression, collagen binding, and platelet GPIbα binding were studied through ELISA assays. Multimer analysis was performed by gel electrophoresis. RESULTS: Bleeding scores were elevated for all subjects except for the p.P1162L and p.R1374C variants. Although all had reduced VWF ristocetin cofactor activity/VWF antigen ratios on plasma testing, recombinant VWF did not show a classic type 2M phenotype for any of the five variants. Homozygous expression of variants p.D1283Y, p.R1349C, p.R1374C, and p.I1453N was consistent with type 2A VWD, although all had normal expression as heterozygous recombinant VWF. Variant P1162L had normal VWF expression and function, consistent with the lack of bleeding symptoms. CONCLUSIONS: Though originally classified as type 2M VWD, these homozygous recombinant VWF variants do not fulfill complete 2M VWD diagnostic criteria. A better classification schema and improved testing for putative type 2M variants is needed in order to effectively diagnose and treat affected patients.